JUDICIAL BEHAVIOR CONGRUENCE WITH PROCEDURAL FAIRNESS REQUIREMENTS IN CIVIL CASES - Petkevičiūtė-Barysienė, Dovilė; Valickas, Gintautas (Teisė, 2016)
The aim of this study was to evaluate judicial behavior congruence with procedural fairness requirements and its factors in civil cases. Behavior of 106 judges in 181 civil cases was evaluated. An analysis protocol for judicial behavior evaluation was created. 5 procedural fairness requirements were analyzed: ethicality, neutrality, opportunity to express opinion, elucidation, control of comprehension of rights. The results revealed that judicial behavior congruence with procedural fairness requirements is not satisfactory. Following factors of judicial behavior congruence with procedural fairness requirements were established: nature of the case, the participation of representatives of the parties at the hearing, the judge’s gender, legal regulation of procedural justice requirements.